2014
DOI: 10.1194/jlr.m045104
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of apolipoprotein A-IV by the transcription factor CREBH

Abstract: This article is available online at http://www.jlr.org transcription factor that could bind to cAMP response element (CRE) and activate the transcription driven by CREcontaining promoters, such as rat phosphoenolpyruvate carboxykinase (PEPCK) promoter ( 1, 2 ).Recent studies employing genetic ablation of CREBH or in vivo delivery of sequence-specifi c shRNA revealed that CREBH is involved in a variety of physiological functions of the liver. It has been shown that CREBH is proteolytically activated by ER stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(88 citation statements)
references
References 51 publications
3
85
0
Order By: Relevance
“…We have previously shown that CREBH knockout mice exhibit hypertriglyceridemia in association with decreased production of apoA-IV, apoA-V, and apoC-II apolipoproteins 23 . In addition, hepatic CREBH was activated in mice fed with atherogenic Paigen diet or a high-fat and high-cholesterol western diet 26, 27 . We also showed that hepatic apoA-I mRNA level was reduced in CREBH knockout mice, and increased by CREBH overexpression in primary mouse hepatocytes, suggesting the possibility that CREBH might play a role in HDL metabolism 26 .…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that CREBH knockout mice exhibit hypertriglyceridemia in association with decreased production of apoA-IV, apoA-V, and apoC-II apolipoproteins 23 . In addition, hepatic CREBH was activated in mice fed with atherogenic Paigen diet or a high-fat and high-cholesterol western diet 26, 27 . We also showed that hepatic apoA-I mRNA level was reduced in CREBH knockout mice, and increased by CREBH overexpression in primary mouse hepatocytes, suggesting the possibility that CREBH might play a role in HDL metabolism 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Bile diversion abolishes the circadian rhythm of lymphatic apoA-IV output, thus suggesting that bile is a major determinant of the circadian rhythm of lymph apoA-IV, probably due to its necessity for luminal lipid digestion and thus absorption and chylomicron secretion. It should also be noted that lymph apoA-IV output in the fasting state is maintained by bile fl ow, possibly as a supply of phospholipids as well (CREB) family of transcription factors have been shown to increase APOA4 expression ( 36,48 ) and specifi c binding sites for CREBH were identifi ed proximal to both human and mouse APOA4 genes ( 48 ). Interestingly, one of the CREB members, LUMAN (CREB3), increased APOA4 expression ‫ف‬ 5-fold in dendritic cells without affecting other members of the gene cluster ( 36 ), but the physiological importance of apoA-IV protein in these cells remains to be investigated.…”
Section: Circadian Rhythm Of Apoa-iv Synthesis and Secretion By Intesmentioning
confidence: 99%
“…apoAIV expression is increased after the overexpression of CREBH in the liver and in cultured cells. High-fat diet induces steatosis in the liver leading to increased expression of CREBH and apoAIV ( 72,73 ). Fasting is known to induce CREBH and apoAIV expression in the liver.…”
Section: Mtpmentioning
confidence: 99%
“…Recently it has been shown that cAMP responsive elementbinding protein, hepatocyte specifi c (CREBH) regulates apoAIV expression by binding to two CREBH elements present in the apoAIV promoter ( 72 ). CREBH is an ER membrane anchored bZIP transcription factor that is mainly expressed in the liver and intestine ( 72,73 ).…”
Section: Mtpmentioning
confidence: 99%
See 1 more Smart Citation